Strong Convergence of Generalized Projection Algorithms for Nonlinear Operators - Chakkrid Klin-eam; Suthep Suantai; Wataru Takahashi (Abstract and Applied Analysis)
We establish strong convergence theorems for finding a common element of the zero point set of a maximal monotone operator and the fixed point set of two relatively nonexpansive mappings in a Banach space by using a new hybrid method. Moreover we apply our main results to obtain strong convergence for a maximal monotone operator and two nonexpansive mappings in a Hilbert space.